RESEARCH OF FEATURES OF MARKETING STRATEGY IN EDUCATION MARKET - N. Zemlyanskaya; N. Kazakova; V. Kolosova (Вестник университета)
The features of marketing strategy in domestic education market are considered. The methods of provision of educational services through distribution channels and strategic decisions on marketing complex elements in this sphere are revealed. The essence of the price policy as a complex of actions for maintenance of optimum level of prices and to variation of its depending on a status of the market and the situation on in it of an educational institution is opened. The considerable attention is paid to a wasteful method of pricing as to the most widespread in this sphere.